The Impact of Modernization on Education in The Society 5.0 Era - Nisya, Wirdatun; Firman, Firman; Sidik, Mohd. Suhadi Bin Mohamed (Fakultas Agama Islam Universitas Wiralodra, 2024)
The Era of Society 5.0 brings impact to life man. Educational institutions expected tough in face obstacles and challenges as well as changes that arise in environment public Good in scope local, regional, national, or environment global society. Purpose of the article This For know impact modernization in education in the era of society 5.0 with use method study studies literature, with exists linkages between modernization and education of course also bring impact good and bad specifically for participant educate. Research result find exists impact positive and negative modernization to education. One of unique characteristics _ use technology artificial intelligence (AI). Welcoming the era of Society 5.0, it is necessary culture education that supports it impact positive with the more open and spread information like create method more learning_diverse. Negative impact happen change conflicting behavior, ethics, norms, rules, or morals of life with ethics, norms, rules and morals of life that exist in society.